FIRM VALUE PERFORMANCE: PROFITABILITY PERSPECTIVE AND CAPITAL STRUCTURE AT STATE-OWNED BANK - Kendri Nengah Sukendri; Ni Putu Ari Aryawati (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2021)
This study aims to determine the relationship and influence of profitability variables and capital structure on firm value toward BUMN's bank listed stated-owned enterprises 2014-2018 in Indonesia. The method of determining the sample is pooling data that examines the entire population and found as many as 4 companies using multiple linear regression with SPSS 23.0 analysis technique. Based on the results of the analysis found that profitability has a significant effect on firm value. Capital structure has no significant effect on firm value.